2017
DOI: 10.1111/1346-8138.13990
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of analyzing mucosal human papillomaviruses in cutaneous warts by restriction fragment mass polymorphism

Abstract: Cutaneous human papillomavirus (HPV) types 1, 2, 4, 7 and 57 are reportedly found in cutaneous warts. However, there are few reports that have investigated the prevalence of mucosal HPV types in cutaneous warts. The aim of this study is to investigate the prevalence of mucosal HPV types in patients with cutaneous warts and to determine any association between HPV types and patient characteristics. We analyzed 62 wart samples that were taken from patients who were diagnosed with cutaneous warts, and 30 normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In around 43% of our patients, warts were found in clusters of ≥5, and they caused inconvenience to most patients. These findings are also in agreement with previously published studies [14,19].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In around 43% of our patients, warts were found in clusters of ≥5, and they caused inconvenience to most patients. These findings are also in agreement with previously published studies [14,19].…”
Section: Discussionsupporting
confidence: 94%
“…Another interesting finding was that a large number of patients had had warts for < 6 months. Park et al [19] and Bruggink et al [14] showed that the majority of their patients had had warts for ≥6 months, and Hogendoorn et al [18] showed that the longer the warts had been present, the less likely HPV DNA was detected. Interestingly, there was no significant difference in the clinical and morphological presentation of warts between HPV27b and HPV57c infections, a finding that is in agreement with Hogendoorn et al [18], who showed that more HPV27-infected warts were found in the plantar region.…”
Section: Discussionmentioning
confidence: 99%
“…So far, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS)-PCR-restriction fragment mass polymorphism (RFMP) has been demonstrated to be a high-throughput and economical method. MALDI-TOF MS can be applied in the detection of oligonucleotides, such as DNA methylation and single-nucleotide polymorphisms, , as well as alternative splicing , and analysis of allele-specific expression. , However, HPV genotyping via MALDI-TOF MS RFMP analysis was limited by the tedious separation and purification by conventional slab gel electrophoresis and high-performance liquid chromatography. In addition, concentration of analyte is too low to be detected through MS, which may draw wrong conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 62 wart samples tested, mucosal HPV (84.4%) was majorly present, most of them belonged to the high-risk HPV (67.2%). [ 3 ] Therefore, in this study, attempts were made to detect the type of HPV through different methods and to confirm the presence of the high-risk HPV.…”
mentioning
confidence: 99%